Understanding abortion seeking care outside of formal health care settings in Cape Town, South Africa: a qualitative study - Jane Harries; Kristen Daskilewicz; Tshegofatso Bessenaar; Caitlin Gerdts (BMC, 2021)
Plain language summary Although abortion was legalized in South Africa in 1996, barriers to safe, legal abortion services remain, and women continue to seek abortions outside of the formal healthcare sector. This study explored the decision-making processes that women undertake when faced with an unintended pregnancy, who they discuss and seek help from, and the factors that influence their decision to seek an abortion outside of the formal health care sector. We interviewed 15 women who had obtained an abortion outside of the health care sector in Cape Town, South Africa. Women were aware that abortions were legal and available in public clinics, but they were concerned about negative and judgmental attitudes from health care providers even though some women were aware of the possible health safety issues related to seeking an abortion outside of the clinic setting. Abortion services should adapt to women's needs and offer them options of facility-based care but also self-managed medical abortions under the guidance of health care providers.